Feasibility and clinical utility of daytime polysomnography performed in NICU to diagnose sleep disordered breathing in infants - Andrew Wilson; Max K Bulsara; Shripada Rao; Gareth Baynam; Anne O’Donnell; Karen Waters; Catherine Dunstan; Dimple Goel; Chloe Lappin; Rhiannon Plavsic; Tracey Verstandig; Kellie Francis (BMJ Paediatrics Open)
Objective To assess the feasibility and clinical utility of daytime polysomnography (PSG) in infants <3 months of age.Methods A prospective observational study of a convenience cohort analysing PSGs that were conducted for clinical purposes in infants less <3 months of age, between 1 May 2021 and 31 May 2024. A comparison was made between results for daytime PSG in the neonatal intensive care unit (NICU) and overnight PSG in the sleep laboratory. The type of PSG performed (daytime vs overnight) was based on the workflow of the sleep laboratory. Primary outcomes were successfully completed PSGs (feasibility) and per cent sleep efficiency (clinical utility). Secondary outcomes compared other sleep parameters between groups. Patient and public feedback directly informed the development of the research question and outcome measures.Results Of 60 PSGs, 28 were daytime and 32 were overnight. Daytime studies had a younger age (median 18 vs 55 days, p<0.001) and shorter median recording time (8.2 vs 10.4 hours, p<0.001). All daytime PSGs were successful, indicating feasibility. After adjusting for age at PSG and total recording time, per cent sleep efficiency was equivalent in the two groups (95% CI −12.4 to 5.7; p 0.456), indicating their clinical utility. For secondary outcomes, daytime PSGs had a higher % rapid eye movement (REM) sleep by 9.9% points (95% CI 1.1 to 18.8; p 0.028) compared with overnight PSG. Parameters that were not different included: frequency of spontaneous arousals, REM latency, sleep latency, Apnoea-Hypopnoea Index and Obstructive Apnoea-Hypopnoea Index. A decline in requests for overnight PSGs and a corresponding increase in daytime PSGs over the course of the study were observed.Conclusion Daytime PSGs performed in NICU were feasible and provided clinically useful results in infants <3 months of age. Availability of daytime PSGs performed at the infant’s bedside expands resource capacity and has the potential for cost savings.